Fireflies! - Brinckloe, Julie (New York : Aladdin Paperbacks, 1986)
A young boy is proud of having caught a jar full of fireflies, which seems to him like owning a piece of moonlight, but as the light begins to dim he realizes he must set the insects free or they will die.
"Aladdin picture books"--Cover.
Booklist.
School Library Journal.
Wilson's Children.
2.5.
2.8
Keywords: Fireflies -- Fiction; Fireflies -- Fiction